Retrospective analysis of paediatric lymphomas at Chris Hani Baragwanath academic hospital - Padayachee, R. S (My University, 2015)
Lymphomas are the third most common paediatric malignancy. Paediatric lymphomas (PL) demonstrate unique epidemiological characteristics compared to adult lymphomas with regard to site of involvement, histopathological spectrum, stage of disease and survival outcome. In South Africa (SA), the high prevalence of Human Immunodeficiency Virus (HIV) results in PL with epidemiological characteristics that contrast with those of the developed world. This retrospective study analysed 52 cases of PL at Chris Hani Baragwanath Academic Hospital (CHBAH), National Health Laboratory Service (NHLS), during the time period from 1 January 2007 to 1 June 2013. The epidemiological and pathological data analysed includes the HIV status, gender, age, site of biopsy at disease presentation, histopathological subtypes, stage of disease at presentation, the presence or absence of opportunistic infections and the use of highly active antiretroviral therapy. The prognostic significance of these data parameters was investigated, together with the survival outcomes of the different histopathological subtypes. Of the 52 PL cases analysed, there were 27 (52%) cases of non-Hodgkin lymphoma (NHL) and 25 (48%) cases of classical Hodgkin lymphoma (CHL). Seventeen (33%)patients were HIV seropositive and 35 (67%) were HIV seronegative. NHL was significantly more prevalent in the HIV seropositive group while CHL was more prevalent in the HIV seronegative group (p = 0.0003). The commonest histopathological NHL subtype was BL (44%), which occurred predominantly in the HIV seropositive group (p=0.03). Of note are some unusual cases of NHL, which included 3 cases of plasmablastic lymphoma (PBL), 2 cases of B-cell lymphoma unclassifiable, with features intermediate between diffuse large B-cell lymphoma (DLBL) and BL and 1 case of T cell/histiocyte rich B-cell lymphoma (THRLBCL). The commonest CHL subtype was nodular sclerosis (40%). The overall male to female ratio was 4.2:1. The overall mean age of the PL cohort was 7.5 years (standard deviation [SD]: 3.5 years), while the mean ages of the NHL cohort and CHL cohort were 7 years (SD: 4 years) and 8 years (SD: 2.8 years) respectively. Lymphoma presentation occurred at a significantly older age in the HIV seropositive NHL group ( mean age of 8.6 years [SD: 3.8] ; median age of 9 years [IQR: 7; ) than the HIV seronegative NHL group (mean age of 5.1 years [SD: 3.5]; median age of 4 years [IQR: 5]; p = 0.03). A conspicuous prevalence of extranodal disease at presentation was found in cases of NHL (92.6%). In the CHL group, the topographic sites of involvement were relatively evenly distributed between nodal (52%) and extranodal regions (48%). Statistical analysis revealed a significantly higher mortality in patients afflicted with NHL (66.7%) compared to CHL (24%) (p = 0.003). No significant influence on survival was demonstrated when assessing the stage of disease in the NHL (p = 0.59) and CHL groups (p = 0.6), nodal versus extranodal topography in CHL (p = 0.14) and the presence of opportunistic infections (p = 0.3). The important findings of this study were the similar survival outcomes of patients in the HIV seropositive and seronegative groups who had NHL and specifically BL. Highly active antiretroviral therapy (HAART) together with chemotherapy administration has improved the prognosis of HIV seropositive PL patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master of Medicine in Anatomical Pathology 2015
Keywords: Paediatric Lymphomas